De trás para frente ou ao contrário : o mangá e a leitura à revelia da escola - Batistella, Danielly (2009)
Originating as charges in the end of the 19th century, developing as comics in the beginning of the 20th century until reaching a reading phenomenon status during the 21st century in the Orient and Occident, the mangá is considered a kind of art one of the most associated to the modern Japan. In this matter, the Japanese imagetic narrative was concreted as part of a cultural aspect integrant in its origin country and started to exert and suffer cultural influences in the Occident countries. This way, mangá s characteristic line and its immediate connection started to be seen as a contemporary reading and a cultural phenomenon, for this, it is in constant transformation and is not only the result of an unthinking consumption or an irrational mode determinated by the communications. Giving this contextualization, this study had as main goal to plot the reader s profile of this new reading phenomenon, to present the mangá as textual genera and to contextualize it about its history, social and cultural aspects. Biographical researches were realized to define the study main theory axis as well as a field research that had as aim to verify what is the part exert by the education institutions in the mangás mediation, a reading support not valued by the school system